CEO’s equity incentives and earnings management - Wang, Shunyu (2017)
This paper explores the relationship between CEOs’ equity incentives and earnings management base on the arguments given by prior studies that CEOs with equity related pay would like to sell shares in the future, which encourage them to manipulate earnings to increase short-term stock price. I hypothesize that the CEOs with stock-related pay would more likely to manipulate earnings. To find the relations between earnings management and CEOs’ equity incentives, discretionary accruals are used as proxies for earnings management. Exercisable options, unexercisable options, option grants, restricted stock awards and stock ownership are used to measure CEOs’ equity incentives. Using the data obtained from Compustat database, I finally find that CEOs with equity incentives would more likely to involve in earnings management behaviors. My results are consistent with the document given by prior studies that CEOs’ stock-related pay create opportunistic incentives for them.